High ankle injury rate in adolescent basketball: A 3‐year prospective follow‐up study. (29th December 2016) - Pasanen, K.; Ekola, T.; Vasankari, T.; Kannus, P.; Heinonen, A.; Kujala, U. M.; Parkkari, J.
Abstract : This prospective study investigated the incidence and pattern of acute time‐loss injuries in young female and male basketball players. Eight basketball teams (n=201; mean age 14.85±1.5) participated in the follow‐up study (2011‐2014). The coaches recorded player participation in practices and games on a team diary. A study physician contacted the teams once a week to check new injuries and interviewed the injured players. In total, 158 injuries occurred. The overall rate of injury (per 1000 hours) was 2.64 (95% CI 2.23‐3.05). Injury rate was 34.47 (95% CI 26.59‐42.34) in basketball games and 1.51 (95% CI 1.19‐1.82) in team practices. Incidence rate ratio (IRR) between game and practice was 22.87 (95% CI 16.71‐31.29). Seventy‐eight percent of the injuries affected the lower limbs. The ankle (48%) and knee (15%) were the most commonly injured body sites. The majority of injuries involved joint or ligaments (67%). Twenty‐three percent of the injuries were severe causing more than 28 days absence from sports. Number of recurrent injuries was high (28% of all injuries), and most of them were ankle sprains (35 of 44, 79%). No significant differences were found in injury rates between females and males during games (IRR 0.88, 0.55, to 1.40) and practices (IRR 1.06, 0.69, to 1.62). In conclusion, ankle and knee ligament injuries were the most common injuries in this study. Moreover, the rate of recurrent ankle sprains was alarming.